PROBLEMATIKA PENDIDIKAN ISLAM DI ERA GLOBALISASI - Syamsul Rijal (Universitas Islam Madura, 2018)
Globalization has many interpretations from various viewpoints. One is the unification effortsof the world community in terms of life style, orientation, and culture. Structural changes and developments that are driving the momentum for globalization beganin the field of economic and technologicalsoonspill overinto the political, social, cultural, lifestyleandso forth. A number of changes and development sthatmark globalization has brought negative consequencesas wellfor thebenefit of mankind. Butifwe examine carefully, that the negative consequencesposed by globalizationis moredominant than theaspect of usefulness. So it canbe said, thatwhenthepeople of the worldand Indonesiain particular, has been in times of crisis. They have beenconfrontedwithanew societywith acapitalistformationscalled globalization. Inthe era of globalization of Islamic education does notneed to beopenorclosed to theambiguityof globalflows. So, whoneeds tobe adhered toby theprinciplesof Islamic educationare: al-Muahafadhah 'ala al-Qadeem al-Salih al-Akhdzu wabial-Jadid al-Ashlah. Modern technologywith allits progressisneutralcase. WhenIslamiceducationis able tofillscience andtechnologywiththeIslamic values​​andsciencetechnologycoursethatwas originallyneutralwill be filledwithreligious values​​.